Breaking fundamental limits of quantum entanglement distribution with quantum switch - XU Ruiqing; ZHOU Rigui; LI Yaochong (Tongxin xuebao)
To solve the problem of low efficiency of entanglement distribution caused by quantum information easily lost in quantum channels, quantum switch was proposed to transmit quantum information. Considering the information transmission capacity of quantum switch, an adaptive entanglement distribution protocol with quantum switch was proposed and two-way entanglement distribution capacity with quantum switch was correspondingly derived. Then the tighter upper bound of channel capacity was derived by using teleportation simulation of quantum channel, the tighter lower bound was derived on the basis of Hash inequality. Simulation result shows that the lower bound of channel capacity in the proposed method generally surpasses the upper bound of which in the traditional quantum channel, providing a feasible thought for delivering high-rate quantum information.